A review on coal-to-electricity policies into practice in northern China. (September 2019) - Li, Zhaoyang; Xu, Zhaowei; Sun, Yuying; Wang, Zhichao; Deng, Shiming; Cui, Yiming; Xu, Wei; Wang, Wei
Abstract: China has been promoting clean energy heating in an all-around way since recent year to reduce air pollution and energy consumption as a result of using coal for winter heating. Supported by a series of Chinese government policies, a coal-to-electricity project become a significant measure for clean energy heating in Beijing-Tianjin-Hebei region and the surrounding areas, which has obviously improved air quality in northern China. The coal-to-electricity project can involve engagement from multiple levels of government and social companies, wherein government is uniquely positioned to provide leadership. However, factors contributing or hindering policies into practice are largely unexplored. This paper presents a review on coal-to-electricity policies into practice through summarizing government policies and practical investigation, including its planning, scope, funding, process, and technical types analysis. In addition, a prospect of coal-to-electricity project in northern China is also given. It is found that the coal-to-electricity project holds a meaningful contribution and promising potential of development given the urgent need for clean energy heating in large areas of northern China. Government financial subsidy is driving force and efficient technical types are carrier. It was further demonstrated that a large amount of government financial subsidy and the application of efficient technology will contribute to the implementation of coal-to-electricity project, which may provide reference for transition of other energy and low carbon policies into practice.